Against The Age (Routledge Revivals) : an Introduction to William Morris. - Faulkner, Peter (Routledge revivals., 2011)
Students new to the work of William Morris will find the full range of his achievements covered here. The author has carefully placed Morris in the context of the Victorian age, but has also suggested the relevance of his ideas today. The six chapters are organised biographically and cover all aspects of Morris's work in poetry, fiction, design and socialist politics.